A Gendered Critique of the Copreneurial Business Partnership: Exploring the Implications for Entrepreneurial Emancipation. (August 2013) - McAdam, Maura; Marlow, Susan
This article explores the gender dynamics of a copreneurial relationship in which the normative gendered order is transposed such that the female partner acts as the lead entrepreneur. This transposition is analysed as an ideological dilemma, given the tensions arising from the conflicting gendered spousal positioning within the business and marital relationships. Drawing on this evidence, the authors explore how entrepreneurship both reflects and reproduces prevailing gendered relationships. Theoretically, the paper contributes to emerging critiques questioning entrepreneurship as a socioeconomic site of agentic emancipation using the conceptual lens of a gendered ideological dilemma.